(untitled) (Universal International Scientific Journal, 2026)
Choosing a career is one of the most important decisions in a person’s life, directly affecting his future lifestyle, professional success and personal well-being. Today, the dynamic development of society, the volatility of the labor market and the diversification of professions require young people to consciously prepare for the process of choosing a career.